"The 'future of conservation' debate: Defending ecocentrism and the Nature Needs Half movement". (January 2018) - Kopnina, Helen; Washington, Haydn; Gray, Joe; Taylor, Bron
Abstract: The Future of Conservation survey, launched in March 2017, has proposed a framework to help with interpreting the array of ethical stances underpinning the motivations for biological conservation. In this article we highlight what is missing in this debate to date. Our overall aim is to explore what an acceptance of ecocentric ethics would mean for how conservation is practised and how its policies are developed. We start by discussing the shortcomings of the survey and present a more convincing and accurate categorization of the conservation debate. Conceiving the future of conservation as nothing less than an attempt to preserve abundant life on earth, we illustrate the strategic and ethical advantage of ecocentric over anthropocentric approaches to conservation. After examining key areas of the current debate we endorse and defend the Nature Needs Half and bio-proportionality proposals. These proposals show how the acceptance of an ecocentric framework would aid both practices and policies aimed at promoting successful conservation. We conclude that these proposals bring a radically different and more effective approach to conservation than anthropocentric approaches, even though the latter purport to be pragmatic. Highlights: Explaining competing ethical underpinnings for nature conservation Critical discussion of the Future of Conservation survey Compelling categorization of ecocentric approaches versus anthropocentric approaches Highlighting the importance of the Nature Needs Half framework